Panitikan a documentary on Philippine literature - Fernandez, Doreen G.; Jacob, Malou L.; Cultural Center of the Philippines (Manila CCP, 1989)
Traces the origins and development of Philippine literature from the riddles, chants and the tanaga through the pasyon of Spanish colonial literature, the poetry and prose of the 19th century nationalist writers, and to the classics of 20th century romanticism, realism and radicalism.
Keywords: Philippine literature -- History